Management of anorectal reverse sinus diseases - Singh, Mahendra Pal (International Surgery Journal, 2022)
Background: It is usual to face complexities in perianal abscesses, fistulas and perianal sinus diseases. Perianal sinus indicates to a blind tract in the perianal area with a discharging opening externally. We selected patients with perianal blind tracts with intra-luminal discharging openings (Reverse sinus) without any visible external opening. Treatment policy was altered accordingly. Methods: We excluded sinuses with external discharging openings, fistulas, hemorrhoids, simple fissures and malignant pathologies. Study was conducted in 64 patients at city hospital, sector-8 Chandigarh. Ours is a hospital based descriptive study conducted between January 2020 to June 2021. Results: Patients with reverse sinuses were divided into four groups based on their etiology. Chronic fissures with discharging opening at 6o clock position (18 cases). Primary anorectal abscesses with intraluminal opening and without any external opening (14 cases). Primary operated anorectal abscess with reverse sinus and no external opening (20 cases). Patients having previous fistula surgery presenting with reverse sinus (12 cases). Treatment in general was tricky yet local healing and long-term results were very good. Conclusions: Once the internal opening is located retrograde probing was done. Perianal nick-incision over the tip of the probe helped to convert sinus into fistula. Subsequent fistulotomy was performed. In case of thick Sphincteric chunk loose seton was encircled around the sphincteric muscle. Subsequently the seton was tightened to achieve cutting and healing simultaneously. In cases of failed retrograde probing perianal nick-incision was given to perform usual probing of the fistula made.